Case report: The use of PRP in the treatment of diabetic foot: case series and a review of the literature - Izzo, Paolo; De Intinis, Claudia; Molle, Marcello; Polistena, Andrea; Sibio, Simone; Codacci-Pisanelli, Massimo; Biacchi, Daniele; Di Cello, Pierfrancesco; Santini, Daniele; Izzo, Luciano; Izzo, Sara (Frontiers in Endocrinology, 2023)
Background: Diabetes mellitus is a prevalent chronic condition that significantly impacts global health. Diabetic foot complications, such as foot ulcers, pose a substantial burden on individuals with diabetes and can lead to serious consequences, including amputation. Platelet-rich plasma (PRP) has emerged as a promising therapeutic approach for enhancing the healing of diabetic foot ulcers. Methods: In our study, we treated 12 patients with chronic diabetic ulcers using PRP injections administered at three-week intervals. Our objective was to assess the reduction in wound size and the rate of complete healing at 6 months after the start of the treatment. Additionally, we conducted a comprehensive literature review to contextualize our findings. Results: Out of the 12 patients, 8 achieved complete healing of their diabetic foot ulcers, while the remaining four showed significant improvement with more than 50% reduction in the initial lesion size. 3 patients developed mild irritation at the inoculation site. These outcomes, combined with the evidence from published studies, highlight the effectiveness of PRP in promoting the healing of diabetic foot ulcers. Conclusion: In conclusion, our study demonstrates the potential of platelet-rich plasma (PRP) as a successful therapeutic option for enhancing the healing process of chronic diabetic foot ulcers. The favorable outcomes observed, including a high rate of complete healing and significant wound size reduction, underscore the value of PRP treatment in managing this challenging complication. Further research and larger studies may provide additional insights into the mechanisms and long-term benefits of PRP in diabetic wound healing.